The Influence of Knowledge And Attitude To Community Compliance With Covid-19 Protocols In Watulimo Village Trenggalek District - Nelsent Oiyan Dimas Karyoto; Nurdina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Coronaviruses are a large family of viruses that cause disease in humans and animals. The disease is mainly spread between people through respiratory droplets from coughs and sneezes. This virus can survive up to three days with plastic and stainless steel SARS CoV-2 can last up to three days, or in aerosols for three hours (Gorbalenya, 2020). The research design was an observational quantitative study with a cross sectional approach with the focus of the research being aimed at analyzingthe influence of knowledge and attitudes of transmission on compliance with the Covid-19 protocol in the community in Watulimo Village, Trenggalek Regencywith a population of 164 respondents and a sample of 115 respondents who were drawn using the simple random sampling technique. The findings show that hNearly half of the respondents had moderate knowledge of 47 respondents (40.5%). Nearly half of the respondents had a moderate attitude as many as 47 respondents (40.5%). Most of the respondents did not comply with the health protocol as many as 84 respondents (73.3%).The results of the study used the test Multiple linear regression shows that with a p-value of 0.000 <0.05, H1 is accepted, so it can be concluded that simultaneously it exists the influence of knowledge and attitudes of transmission on compliance with the Covid-19 protocol in the community in Watulimo Village, Trenggalek Regency with a magnitude of influence of 80.1%. It is hoped that the community can comply with health protocols as appropriate which must use standard masks, maintain distance and be diligent in washing hands with soap. That way it can reduce the risk of spreading the Covid-19 virus.